Networks of Collaboration in Oligopoly - Sanjeev Goyal; Sumit Joshi (Tinbergen Institute, 2000)
In an oligopoly, prior to competing in the market, firms have an opportunity to form pair-wisecollaborative links with other firms. These pair-wise links involve a commitment of resources andlead to lower costs of production of the collaborating firms. The collection of pair-wise linksdefines a collaboration network. We study the architecture of strategically stable networks.Our analysis reveals that in a setting where firms are ex-ante identical, strategically stablenetworks are often asymmetric, with some firms having a large number of links while others havefew links or no links at all. We characterize such asymmetric networks; the dominant grouparchitecture, stars, and inter-linked stars are found to be stable. In asymmetric networks, thefirms with many links have lower costs of production as compared to firms with few links. Thuscollaboration links can have a major influence on the functioning of the market.
Keywords: 330; Oligopol; Wettbewerbsbeschränkung; Forschungskooperation; Unternehmensnetzwerk; Theorie